Application of electrolyzer to alleviate power fluctuation in a stand alone microgrid based on an optimal fuzzy PID control - Ngamroo, Issarachai (My University, 2012)
Due to the high intermittent power generations from wind and photovoltaic in the microgrid (MG) system, these result in the severe power fluctuation. When the fuel cell (FC) equipped with the aqua electrolyzer (AE) has been installed in the MG, in addition to hydrogen production for FC, the absorbed power by AE can be controlled to alleviate the power fluctuation. This paper proposes the coordinated control of AE and FC to solve the power fluctuation problem in the MG. By control of the power absorption by AE and the power production by FC, the power fluctuation in the MG can be suppressed. The optimal fuzzy logic based-proportional-integral-derivative (FLPID) is used to design the controllers of AE and FC. Without trial and error as in the conventional FLPID controller design, scale factors, membership functions and control rules of the optimal FLPID controller are automatically and simultaneously tuned by a bee colony optimization. Simulation results confirm the superior stabilizing effect of the proposed optimal FLPID controller in comparison with the conventional FLPID controller under several system disturbances. © 2012 Elsevier Ltd. All rights reserved.
Keywords: Aqua electrolyzer; Bee colony optimization; Fuel cell; Fuzzy PID control; Microgrid